Use of modern pedagogical technologies during distance learning in higher educational institutions - Deinichenko, O.; Дейніченко, Олена Валеріївна (Одеса : МЦНД, 2020)
The main purpose of vocational education is to train a qualified specialist capable of effective professional work in the specialty, as well as the formation and development of personal qualities necessary for her and society for socially significant activities.
Keywords: тези доповідей